1985
DOI: 10.1007/bf00283139
|View full text |Cite
|
Sign up to set email alerts
|

Real and artefactual erythrocyte swelling in hyperglycaemia

Abstract: Summary.The mean erythrocyte volume of ~ patients with acute diabetic decompensation was determined by Coulter measurement and found to be elevated above normal (mean increase 5.5 Ix3). Experiments in vitro revealed this to be an artefact associated with Coulter determination. A more reliable estimate of in vivo erythrocyte volume can be obtained from centrifugated haematocrit and erythrocyte count. With this method, true erythrocyte swelling parallel to glucose concentration was observed when erythrocytes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The mean corpuscular volume (MCV) value of diabetic women was smaller than in non‐diabetic women (Table 1), possibly due to the tendency to microcytosis driven by lower iron levels in the female diabetic group (Table 1) and in women with poor glycaemic control (Table 2). It is an interesting result, as other authors have reported that erythrocytes from diabetics are bigger than those from non‐diabetics 40‐43 . These findings were obtained either by Atomic Force Microscopy 40,41 or automated haematological analyser by the Coulter method, 42,43 like our case.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The mean corpuscular volume (MCV) value of diabetic women was smaller than in non‐diabetic women (Table 1), possibly due to the tendency to microcytosis driven by lower iron levels in the female diabetic group (Table 1) and in women with poor glycaemic control (Table 2). It is an interesting result, as other authors have reported that erythrocytes from diabetics are bigger than those from non‐diabetics 40‐43 . These findings were obtained either by Atomic Force Microscopy 40,41 or automated haematological analyser by the Coulter method, 42,43 like our case.…”
Section: Discussionsupporting
confidence: 75%
“…It is an interesting result, as other authors have reported that erythrocytes from diabetics are bigger than those from non-diabetics. [40][41][42][43] These findings were obtained either by Atomic Force Microscopy 40,41 or automated haematological analyser by the Coulter method, 42,43 like our case.…”
Section: Rdw Iron MCV and Reticulocytesmentioning
confidence: 85%
“…Increased MCV (= mean corpuscular volume) has been found in patients with decompensated diabetes (Mohr 1938;Strauchen et al 1981;Evan-Wong & Davidson 1983) and in diabetic patients compared to normal subjects (Davidson et al 198 1). Although methodical inaccuracies seem to exist in measuring MCV (Beautyman 1982;Ernest 1982), Bock et al (1985) came to the conclusion that macrocytosis does exist in hyperglycaemic patients. Furthermore, np is related to the amount of plasma proteins (Barer &Joseph 1954), and disturbances in the composition of proteins and plasma viscosity are well recognized in diabetes (Ditzel & Moinat 1959;McMillan 1974;Barras 1981;Ewan-Wong & Davidson 1983).…”
Section: The Intensity Of the Reflex (Ir)mentioning
confidence: 99%
“…hyperglycaemia and hyperlipidaemia may depress serum sodium concentrations, thereby mimicking hyponatraemia [59]. Mean cell haemoglobin concentration and haematocrit determined using Coulter Counters ® may be artificially elevated due to osmotic swelling of erythrocytes in the isotonic buffer used during the analysis [60]. Plasma creatinine concentrations may be misleading as a parameter of renal function due to chemical interference of acetoacetate with the creatinine measurement in commonly employed methods for serum creatinine assay.…”
Section: Pitfalls In Diagnosismentioning
confidence: 99%